Analisis Literatur Tentang Kontribusi Minat dan Motivasi Belajar Terhadap Prestasi Akademik Siswa Tingkat SMP - Didit Darmawan; Safira Martania Putri; Dzakiyatul Fuada (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2026)
This study aims to analyze the contribution of learning interest and learning motivation to the academic achievement of junior high school students through a systematic literature review approach. The study is motivated by the relatively low academic performance of students and the importance of affective factors in supporting learning success. The research employed a qualitative approach with a systematic literature review (SLR) design following PRISMA guidelines, using scientific articles published between 2020 and 2025 as data sources. The findings indicate that learning interest and learning motivation have a predominantly positive and significant relationship with students’ academic achievement. Learning interest functions as an initial trigger for student engagement in the learning process, while learning motivation sustains continuous learning efforts. However, variations in findings suggest the influence of contextual factors such as learning environment, teaching methods, and individual student characteristics. This study contributes theoretically by strengthening the integration of interest and motivation concepts in educational psychology, and practically by providing insights for teachers and educational institutions in designing adaptive, student-centered learning strategies.